K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 7 2016

a)  \(2^{225}=\left(2^3\right)^{75}=8^{75}\)

      \(3^{150}=\left(3^2\right)^{75}=9^{75}\)

vì 8 < 9 và 75 = 75 

=> 875 < 975

=> 2225 <  3150

b)  \(2^{91}>2^{90}=\left(2^5\right)^{18}=32^{18}>25^{18}=5^{36}>5^{35}\)

\(\Rightarrow2^{91}>5^{35}\)

c) \(5^{300}=\left(5^3\right)^{100}=125^{100}\)

     \(3^{500}=\left(3^5\right)^{100}=243^{100}\)

Vì 125 < 243 mà 100 = 100

=> \(5^{300}< 3^{500}\)

15 tháng 7 2016

Bài nì lp 6 lm nhìu rùi mà

Ta có:

+ 2225 = (23)75 = 875

3150 = (32)75 = 975

Vì 875 < 975

=> 3225 < 3150

+ 291 = (213)7 = 81927

535 = (55)7 = 31257

Vì 81927 > 31257

=> 291 > 535

+ 5300 = (53)100 = 125100

3500 = (35)100 = 243100

Vì 125100 < 243100

=> 5300 < 3500

\(a,35:\left(\frac{-5}{3}\right)+2\frac{1}{2}:\left(-\frac{5}{3}\right)=35.\left(-\frac{3}{5}\right)+\frac{5}{2}.\left(-\frac{3}{5}\right)\)

\(=-21+-\frac{3}{2}\)

\(=\frac{-42-3}{2}=-\frac{45}{2}\)

\(b,\frac{10^3+2.5^3+5^3}{55}=\frac{\left(2.5\right)^3+2.5^3+5^3}{5.11}\)

\(=\frac{5^3\left(2^3+2+1\right)}{5.11}\)

\(=\frac{5^2\left(8+2+1\right)}{11}\)

\(=\frac{5^2.11}{11}=5^2=25\)

\(C,\frac{27^2.2^5}{6^6.32^3}=\frac{\left(3^3\right)^2.2^5}{\left(2.3\right)^6.2^5}\)

\(=\frac{3^6}{2^6.3^6}=\frac{1}{2^6}=\frac{1}{64}\)

31 tháng 1 2017

a/\(^{2867971991^{-10}}\)

b/\(^{1125899907^{-55}}\)

c/\(^{1693508781^{-05}}\)

d/\(^{2867971991^{-10}}\)

3 tháng 9 2016

Ta có:

291 = (213)7 = 81927

535 = (55)7 = 31257

Do 8192 > 3125 nên 81927 > 31257

Vậy 291 > 535

               

3 tháng 9 2016

Ta có:

\(2^{91}=\left(2^{13}\right)^7=8192^7\)

\(5^{35}=\left(5^5\right)^7=3125^7\)

Vì \(8192^7>3125^7\left(8125>3125\right)\) nên \(2^{91}>5^{35}\)

Vậy \(2^{91}>5^{35}\)

19 tháng 9 2016

a)\(\left(x-\frac{5}{3}\right)^2=\frac{49}{16}\)

    \(\left(x-\frac{5}{3}\right)^2=\left(\frac{7}{4}\right)^2=\left(-\frac{7}{4}\right)^2\)

\(\Rightarrow\left[\begin{array}{nghiempt}x-\frac{5}{3}=\frac{7}{4}\\x-\frac{5}{3}=-\frac{7}{4}\end{array}\right.\)\(\Rightarrow\left[\begin{array}{nghiempt}x=\frac{41}{12}\\x=-\frac{1}{12}\end{array}\right.\)

               Vậy \(x=\frac{41}{12}=-\frac{1}{12}\)

19 tháng 9 2016

b)2x29=3x35

   \(\Rightarrow\frac{x^{29}}{3}=\frac{x^{35}}{2}\)(thiều trường hợp)